The Protective Effect of Sevoflurane Conditionings Against Myocardial Ischemia/Reperfusion Injury: A Systematic Review and Meta-Analysis of Preclinical Trials in in-vivo Models - Hu, Bin; Tian, Tian; Hao, Pei-Pei; Liu, Wei-Chao; Chen, Ying-Gui; Jiang, Tian-Yu; Xue, Fu-Shan (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective: Myocardial ischemia/reperfusion injury (IRI) is a common and serious complication in clinical practice. Sevoflurane conditionings have been identified to provide a protection against myocardial IRI in animal experiments, but their true clinical benefits remain controversial. Here, we aimed to analyze the pre-clinical evidences obtained in animal models of myocardial IRI and explore the possible reasons for controversial clinical benefits. Methods: Our primary outcome was the difference in mean infarct size between sevoflurane and control groups in animal models of myocardial IRI. After searching the databases of PubMed, Embase, Web of science and Cochrane library, a systematic review retrieved 37 eligible studies, from which 28 controlled comparisons of sevoflurane preconditioning (SPreC) and 40 controlled comparisons of sevoflurane postconditioning (SPostC) were made in a pooled random-effects meta-analysis. In total, this analysis included data from 313 control animals and 536 animals subject to sevoflurane conditionings. Results: Pooled estimates for primary outcome demonstrated that sevoflurane could significantly reduce the infarct size after myocardial IRI whether preconditioning (weighted mean difference (WMD): -18.56, 95%CI: -23.27 to -13.85, P < 0.01; I2 = 94.1%, P < 0.01) or postconditioning (WMD: -18.35, 95%CI: -20.88 to -15.83, P < 0.01; I2 = 90.5%, P < 0.01) was performed. Interestingly, there was significant heterogeneity in effect size that could not be explained by any of the prespecified variables by meta-regression and stratified analysis. However, sensitivity analysis still identified the cardioprotective benefits of sevoflurane conditionings with robust results. Conclusions: Sevoflurane conditionings can significantly reduce infarct size in in vivo models of myocardial IRI. Given the fact that there is the lack of consistency in the quality and design of included studies, more well-performed in vivo studies with the detailed characterization of sevoflurane protocols, especially studies in larger animals regarding cardioprotection effects of sevoflurane, are still required.